The new Brazil - Roett, Riordan, 1938-; Brookings Institution (Washington, D.C. : Brookings Institution Press, 2010)
"Recounts Brazil's evolution from remote Portuguese colony, through economic crises that led to more prudent monetary policies, and to its new status as a regional leader, a respected ambassador for the developing world, and an increasingly important partner for the United States and European Union"--Provided by publisher.
Introduction: The new Brazil -- The historical background : colony, empire, and republic -- The making of modern Brazil, 1930-64 -- The 1964 revolution : from bureaucratic authoritarianism to Abertura -- The incomplete transition, 1985-94 -- The Cardoso Era, 1995-2002 -- Lula's Brazil -- Brazil's emergence on the global stage -- Conclusion: Brazil emergent
Includes bibliographical references and index.
Keywords: Brazil -- Economic conditions -- 1985-; Brazil -- Economic policy -- 2003-; Brazil -- Foreign economic relations; Brazil -- Foreign relations -- 1985-